1992
DOI: 10.3109/01480549209014162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rumen Fermentation on Response to Endophyte—Infected Tall Fescue Seed Measured by a Rat Bioassay

Abstract: Possible alteration of toxicity of endophyte-infected tall fescue by ruminal fermentation was studied using 28 Harlan Sprague-Dawley rats (avg. initial wt., 141 g). These were assigned randomly to one of four treatments in a 2*2 factorial consisting of a 14-day growth period with weights and feed consumption data determined on days 0, 5, 10 and 14. Treatments were: endophyte-infected Kentucky-31 tall fescue seed (E+) or endophyte free Johnstone tall fescue seed (E-) that was incubated for 0 (NON) or 24 hours (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As the ergopeptine alkaloids are charged at low pH, one may assume that these compounds would not be absorbed in the abomasum (Eckert et al, 1978). Thus, absorption of these compounds would appear to be limited to the small intestine in nonruminants (i.e., duodenum and jejunum; Rothlin, 1933) and the forestomach (Westendorf et al, 1992;Hill et al, 2001) and intestine in ruminants. The rumen is unlike the gastric stomach; the pH is near neutral in forage-fed animals; and a mucosal layer is not necessary to protect the tissue from the digesta (Russell and Rychlik, 2001).…”
Section: Absorptionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the ergopeptine alkaloids are charged at low pH, one may assume that these compounds would not be absorbed in the abomasum (Eckert et al, 1978). Thus, absorption of these compounds would appear to be limited to the small intestine in nonruminants (i.e., duodenum and jejunum; Rothlin, 1933) and the forestomach (Westendorf et al, 1992;Hill et al, 2001) and intestine in ruminants. The rumen is unlike the gastric stomach; the pH is near neutral in forage-fed animals; and a mucosal layer is not necessary to protect the tissue from the digesta (Russell and Rychlik, 2001).…”
Section: Absorptionmentioning
confidence: 97%
“…The adaptive value of this symbiosis is that the first enzymes that act on the feed are not mammalian, but microbial, and catabolize substrates that are not otherwise catabolized by the host animal (e.g., cellulose). An early hypothesis stated that the rumen was the principal site of alkaloid degradation (Westendorf et al, 1992;Hill et al, 2001). The rumen flora detoxify several mycotoxins, including ochratoxin A, deoxynivalenol, and zearalenone (Kiessling et al, 1984;Fink-Gremmels, 2008).…”
Section: Metabolismmentioning
confidence: 98%
“…There are no data describing the bioavailability of ergovaline from ryegrass leaf or seed head. In vitro fermentation studies with tall fescue have demonstrated that feeding rats a whole seed that was previously incubated with rumen fluid is less toxic than feeding a seed not incubated, which suggests that rumen microflora reduced the concentration of toxic compounds (Westendorf et al 1992). Using in vitro fermentation of rumen fluid containing added pyrrolizidine alkaloids, Westendorf et al (1993) reported that pyrrolizidine alkaloids were degraded by rumen fermentation.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…When tall fescue seed was incubated with rumen fluid in an in vitro fermentation study conducted by Westendorf et al (1992), the diet that had been previously incubated with fluid was less toxic to rats consuming the whole seed than those that were fed a non-ruminal fluid incubated fescue seed. In the same study, authors determined that rats consuming the rumen fluid inoculated endophyte-infected seed had improved gain: feed conversion compared to those with non-incubated seed (1992).…”
Section: B Ergot Alkaloids and Rumen Microbiomementioning
confidence: 99%
“…This suggests that the rumen microbiota are responsible for reducing some of the toxicity of the endophyte, in agreement with results by De Lorme et al (2007). However, the results from Westendorf et al (1992), De Lorme et al (2007 and the bacteria isolated by , were accessed from rumen fluid conducted as an in vitro or ex vivo experiment, rather than in vivo where additional physiological parameters can be measured for efficacy.…”
Section: B Ergot Alkaloids and Rumen Microbiomementioning
confidence: 99%